Análise da aplicação de conectores de cisalhamento em chapa de aço com recortes regulares para transmissão de esforços em pilares mistos de seção retangular preenchidos com concreto - Larice Gomes Justino Miranda (2024)
Concrete-filled steel tube columns are structural elements consisting basically of an external steel tube and a concrete core, whose interaction improves the strength and ductility of the column and favors energy absorption and fire resistance, thus configuring a suitable solution for high-rise buildings, bridges and earthquake-prone buildings. However, despite the widely use of this structural solution, there is still a need for the study and development of solutions for the connection between steel or composite beams and filled columns that are simple, structurally effective and provide an efficient transmission of loads regarding the composite behavior of the column. Given this need and the success of the application of continuous shear connectors, also known as composite dowels, as a mechanism of load transfer in filled composite columns of circular section, it was analyzed, in this work, their application in rectangular filled composite columns. To study the proposed solution, experimental tests were carried out on six specimens of filled composite columns, three of them with a cross section of 400 mm x 400 mm and another three with a cross section of 500 mm x 500 mm, four specimens consisting of Crestbond connectors and two consisting of clothoidal connectors. Subsequently, a parametric study was developed, based on a validated finite element model, consisting of 46 models of each type of connector, in which it was observed that the parameters that have the greatest influence on the maximum load value are the thickness of the connector, the dowel spacing and the yield strength of the connector steel and that the relationship between the maximum load value and the number of steel dowels characterizes a linear function. Finally, formulations were proposed to predict the resistant capacity of these connections for limit situations in which there is no restriction on the movement of the connector in the direction of the beam and when this restriction is total. The proposed equations, in addition to adjusting to the experimental values, with correction factor equal to unity and coefficient of variation around 10 %, present the terms physically related to the failure mode observed in the tests.